A Standardised Gaited Field Test Produces Changes in Blood Biomarkers and Heart Rate in Four‐Beat Gaited Horses. (June 2014) - Silva, F; Melo, S; Abreu, J; Manso, H; Manso Filho, H
Abstract : Introduction: There is little information about biochemical and physiologic responses to exercise in Brazilian gaited horses. The aim of this study was to evaluate blood biomarkers and heart rate (HR) in gaited horses during a standardized gaited field test (SGT). Methods: Sixteen horses performed a SGT (10 min warm‐up, 30 min of marcha gait and 15 min recovery). Blood samples and HR were collected at rest, after warm‐up, after 15 (F + 15) and 30 min (F + 30) of marcha, and after recovery. Assays were performed to measure glucose, lactate, total plasma protein, hematocrit, urea, creatinine, glutamine, glutamate, triglycerides, total cholesterol, Ca, P, Mg, Na, Cl and K. HR was measured using a HR monitor. Results were analyzed using one‐way or two‐way ANOVA. Post‐hoc analyses included the Holm‐Sidak test, Student's t‐tests, and Pearson's correlation analyses. The null hypothesis was rejected when P<0.05. Results: [Glucose] and [lactate] increased during SGT (P<0.05). A significant interaction between phase of SGT and fitness level was observed for [glucose] but not for [lactate]. The SGT also produced increases (P<0.05) in hematocrit, [TPP], [urea], [creatinine], [triglycerides], [P] and [K] and a reduction (P<0.05) in [Ca]. HR increased from ∼47 bpm at rest, to ∼140 bpm at F + 15 and F + 30 (P<0.05). Conclusions: This study documents submaximal aerobic exercise, as performed during the GST is sufficient to alter energy biomarkers in gaited horses. Ethical Animal Research: The study was approved by UFRPE's animal research committee (#62/2007‐CTA/DZ/UFRPE).Sources of funding:  CAPES, IRCA Animal Nutrition and Cascatinha, Recanto da Serra, Annette and Abreu horse farms.Competing interests:  none.